Pengaruh Financial attitude dan Financial Knowledge Terhadap Financial Management Behavior - Manalu, Lia Windah Putri; Hasman, Haryaji Catur Putera; Alfifto, Alfifto (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
The purpose of this study was to determine the effect of Financial Attitude and Financial Knowledge on Financial Management Behavior in Management Study Program Students at Sari Mutiara Indonesia. This type of researh is associative quantitative. The population in this study werw undergraduate students of The Manajement Study Program at Sari Mutiara Indonesia University in 2019 as many as 226 students.This study used a sampling technique, namely non-probability sampling of 145 respondents, namely undergraduate students of the Management Study Program at Sari Mutiara Indonesia University in 2019. The data collection technique in this study was to distribute questionnaires via Google Form. The result of this study of this study indicate that Financial Attitude has a positive and significant effect on Financial Management Behavior with a tvalue of 5.295 ttable 1.976 and a significance of 0.001 0.05. financial Knowledge has a positive and significant effect on Financial Management Behavior with a tvalue of 2.130 ttable 1.976 and a significance of 0.001 0.05. Financial Attitude and Financial Knowledge have a positive and significant effect on Financial Management Behavior with an Fvalue of 15.089 Ftable 2.34 and significance 0.001 0.05. The coefficient of determination obtained is 16.4%, the remaining 83.6% is influenced by other variables.